PENGGUNAAN PUPUK ORGANIK CAIR DAUN GAMAL TERHADAP PERTUMBUHAN BIBIT BATANG BAWAH KARET KLON PB 260 (Hevea brasiliensis Muella Arg) - Nurhayati Nurhayati; Assrorudin Assrorudin; Wina Erviana (Journal of Agro Plantation (JAP), 2022)
Rubber plants (Hevea brasiliensis Muell. Arg) have an important role for the Indonesian economy, where the area of ​​rubber plantations in Indonesia reaches 3.6 million hectares. The low productivity of rubber plants in Indonesia, it is necessary to increase the productivity of rubber through the provision of seeds for the propagation of rubber plants. The use of POC in Gamal leaves can encourage good rootstock growth with optimal roots, because Gamal leaf tissue contains 3.15% N, 0.22% P, 2.65% K, 1.35% Ca and 0.41% Mg. The aim of this study was to determine the effect of giving Gamal leaf POC on rubber rootstock seedlings of clone PB 260. This research was conducted in the experimental garden of the Ketapang State Polytechnic, Jl. Rangga Sentap Dalong, Sukaharja Village, Delta Pawan sub-district, Ketapang district, West Kalimantan, from October 2021 to January 2022 at the Ketapang State Polytechnic. This study used a non-factorial Completely Randomized Design (CRD) with 6 treatments and 4 replications with 3 plant samples so that 72 seedlings were obtained. Observation parameters included plant height (cm), number of umbrellas (strands), stem diameter (mm), root length (cm), plant dry weight (g). The results showed that the administration of POC of Gamal leaves on rubber rootstock seedlings treated with P5 (400 mL of POC of Gamal leaves + 500 mL of water/polybag) was able to increase the growth of plant height, stem diameter and root length.